1988
DOI: 10.1088/0953-4075/21/6/002
|View full text |Cite
|
Sign up to set email alerts
|

Autoionisation of N5+(3ln'l') for n'=3-10: experiment and theory

Abstract: The energy values of the autoionisation states (3h'l') of the N5+ ion are deduced from the analysis of ejected-electron spectra following the collisional electron charge transfer process between bare N7+ projectiles and various targets (He, H, and Ar). We compare these results with our ab initio theoretical calculations employing a fourteen-state pseudostate close-coupling scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Such structures were partly due to, according to our calculations, the 3 F o (4), 1 F o (3), 1 F o (4), 1 F o (7) and 1 F o (8) states with energies of 77.10, For resonances below the N = 4 threshold, we compare our results in tables 12 and 13 with those in the literature for O 6+ and Ne 8+ , respectively. In table 12, we compare our 1,3 F o (4 5 ) states for O 6+ with those of van der Hart et al (1994). In general, the agreements are quite good, with the exception of the widths for the 1 F o (6) and 1 F o (7) states.…”
Section: Present Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…Such structures were partly due to, according to our calculations, the 3 F o (4), 1 F o (3), 1 F o (4), 1 F o (7) and 1 F o (8) states with energies of 77.10, For resonances below the N = 4 threshold, we compare our results in tables 12 and 13 with those in the literature for O 6+ and Ne 8+ , respectively. In table 12, we compare our 1,3 F o (4 5 ) states for O 6+ with those of van der Hart et al (1994). In general, the agreements are quite good, with the exception of the widths for the 1 F o (6) and 1 F o (7) states.…”
Section: Present Resultsmentioning
confidence: 80%
“…The resonance positions between these two calculations differ to within 0.2 eV, with the exception of the 3 F o (1) state having a difference of slightly more than 0.2 eV. Also, Oza et al (1988) did not report results for all the doubly excited n n states with n = 3, n 5. According to our calculations, the states they calculated…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…In their work, Tsurubuchi et al [1] have observed a peak corresponding to (3/3 l') autoionisation states of N 5 + by performing energy gain spectroscopy of the fast ion in the collisions between N 7+ and He. By collision between bare N 7 + ions and a two electron target (He and H2), Bordenave-Montesquieu et al [2][3] have observed in ejected electron spectra excited states formed by two-electron capture, which states are autoionising configurations of N s+ (nln'l') with n = 2, 3, 4 and n'> n. Others experimental investigations on the He-like nitrogen ion have also been made by Benoit-Cattin et al [4], Oza et al [5], and by MorettoCapelle et al [6].…”
Section: Introductionmentioning
confidence: 95%